Causes of the extreme cold event in December 2023 on Eastern China - Baoxu Chen; Hongyan Cui; Fangli Qiao; Ziqun Zhang; Xiaohui Sun; Chang Gao; Yang Song (Environmental Research Communications, 2024)
An extreme cold event outbreaks in Eastern China (EC) in December 16–22, 2023. Its maximum intensity (−8.30 °C) and duration (7 days) are in the second place in December during 1980–2023. In Early Stage (December 6–10), surface air temperature (SAT) anomalies reach the highest at 6.77 °C, exceeding mean value by two standard deviations. The variation of SAT anomalies (differences of SAT anomalies between the last day and the first day for a given period) is 0.60 °C. In Development Stage (December 11–15), SAT anomalies begin to decline but remain positive. In Outbreak Stage (December 16–22), the variation of SAT anomalies reaches a minimum of −3.17 °C, reflecting the cooling of EC. From December 1, cold air gradually gathers in Siberia under the influence of Arctic high moving southward. Cold air is locked in Siberia due to negative anomalies of geopotiential height (GH) and the westerlies anomalies between 40°–50°N. On December 11, these negative GH anomalies begin to move southeastward, and the westerlies anomalies weaken to a easterlies. From December 16–22, EC experiences an extreme cold event due to the southward of Arctic high and the eastward of Ural and Okhotsk high. On the basis of the zonal wind index (ZI) phase changes from negative to positive and the jet stream moves southeastward, the strong (weak) jet stream is spotted to block (promote) the southward of cold air. Linear regression shows that negative Arctic Oscillation (AO) conducts to the concentration of cold air in Siberia. Positive Siberia High (SH) pushes cold air to EC. SAT anomalies decrease by 2.29 °C in EC with the increase of 1 unit for SH. In empirical orthogonal function (EOF) analysis, EOF1 (28.07%) is characterized by warm Arctic and cold Siberia (WA-CS), which reflects the effect of SH on the occurrence of extreme cold events.